Nash bronepoezd . Our Armoured Train - Ptashuk, Mikhail (Belarusfilm, 1988)
Duration: 02:10:00 At the time of glasnost in the Soviet Union, the movie tells the story of a man who managed to quickly ascend on the social and political ladder of Soviet society under Stalin. In 1966, the main character had to face his Stalinist past. He is haunted by the ghosts of the violent years of the Stalin rule, whom he served so well. Ultimately they ruin everything that he has accomplished throughout his career.